AB0468 The Unique Subset of Monocytes Expressing CD14bright and CD16 is Increased with Disease Activity and Changed with Treatment Response in Patients with Rheumatoid Arthritis. (10th June 2014) - Tsukamoto, M.; Yoshimoto, K.; Seta, N.; Suzuki, K.; Takeuchi, T.
Abstract : Background: We reported that the expression of CD16 on peripheral monocytes was significantly increased in patients with rheumatoid arthritis (RA) compared with healthy controls (HCs). Recently, it has been shown that monocytes were divided into three different subsets based on the expression level of CD14 and CD16. While it has been reported that a subpopulation of CD14bright CD16+ intermediate monocytes is increased in RA patients, it is not clear whether this unique subset of monocytes is changed by treatment with a possible association with clinical response. Objectives: The purpose of this study is to investigate the association between the percentage of peripheral CD14bright CD16+ intermediate monocytes, CD14bright CD16- classical monocytes, or CD14dim CD16+ nonclassical monocytes and disease activity or clinical response to methotrexate (MTX) treatment in RA patients. Methods: Consecutive RA patients who fulfilled the 2010 ACR/EULAR RA Classification Criteria were included in the study. Among the registered patients, 34 RA patients (28 females and 6 males) had more than moderate disease activity (DAS28-ESR 3.2) at baseline and received MTX treatment, but not biologics, and then their peripheral blood samples and clinical records were obtained just before and at 12 weeks after MTX treatment. Peripheral blood samples were also obtained from 14 healthy volunteers (11 females and 3 males) as control. The expression levels of CD14 and CD16 on monocytes were measured by flow cytometric analysis and divided into 3 subsets based on the expression level of CD14 and CD16 as previously reported. The clinical response to MTX treatment was evaluated using the EULAR response criteria based on the relative change in DAS28-ESR from baseline to 12 weeks. Results: The mean age of the patients was 59.3±12.6 years. The mean DAS28-ESR score was 4.9±0.9. The mean MTX dose was 11.0±3.3 mg a week at 12 weeks after initiation of MTX treatment. There was no significant difference in backgrounds between RA patients and HCs. Flow cytometric analysis revealed that intermediate monocytes were significantly (p<0.001) increased in RA patients before treatment (14.8±6.6%) compared with HCs (7.5±1.7%), whereas classical monocytes were significantly (p<0.001) decreased (70.9±9.2% vs 82.1±5.6%). Moreover, the proportion of intermediate monocytes was significantly correlated with DAS28-ESR before and after the treatment (r=0.49, p=0.003 and r=0.47, p=0.006, respectively). We also found that the proportion of intermediate monocytes was significantly decreased in good responders, but not in moderate or no responders to MTX (p=0.004 and 0.10, respectively). Finally, the difference in the proportion of intermediate or classical monocytes between RA patients and HCs disappeared after treatment (p=0.06). Conclusions: Intermediate monocytes were increased in RA patients with moderate or high disease activity compared with HCs. Furthermore, intermediate monocytes were significantly decreased in good responders to MTX treatment. These results indicate that intermediate monocytes may play an important role in the pathogenesis of RA, such as production of inflammatory cytokines. References: ACR2013, #2420 Ann Rheum Dis.2011;70:1052 Arthritis Rheum.2012;64:671 Immunol Res.2012;53:41 Disclosure of Interest: M. Tsukamoto: None declared, K. Yoshimoto: None declared, N. Seta: None declared, K. Suzuki: None declared, T. Takeuchi Grant/research support: Abbott Japan Co., Ltd., Astellas Pharma, Bristol-Myers K.K., Chugai Pharmaceutical Co., Ltd, Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Nippon Shinyaku Co., Ltd., Otsuka Pharmaceutical, Pfizer Japan Inc., Sanofi-aventis K.K., SantenPharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., Consultant for: Abbott Japan Co., Ltd., Bristol-Myers K.K., Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi TanabePharma Co., Pfizer Japan Inc., Takeda Pharmaceutical Co., Ltd., Astra Zeneca, K.K., Eli-Lilly Japan K.K., NovartisPharma K.K., Asahi Kasei Medical K.K. DOI: 10.1136/annrheumdis-2014-eular.5101